Near-UV light emitting diode with on-chip photocatalysts for purification applications. Issue 17 (3rd August 2022) - Leem, Young-Chul; Myoung, NoSoung; Hong, Sang-Hyun; Jeong, Sehee; Seo, Okkyun; Park, Seong-Ju; Yim, Sang-Youp; Kim, Joon Heon
Abstract : An array of TiO2 nanodisks combined with SiO2 pedestals is fabricated directly on the surface of an InGaN-based near-ultraviolet LED to enhance photocatalytic activity for purification of organic dye molecules. Abstract : A new design for light-emitting diodes (LEDs) with on-chip photocatalysts is presented for purification applications. An array of disk-shaped TiO2, with a diameter of several hundred nanometers, combined with SiO2 pedestals was fabricated directly on the surface of an InGaN-based near-ultraviolet (UV) LED using a dry etching process. The high refractive-index contrast at the boundary and the circular shape can effectively confine the near-UV light generated from the LED through multiple internal reflections inside the TiO2 nanodisks. Such a feature results in the enhancement of light absorption by the photocatalytic TiO2 . The degradation of the organic dye malachite green was monitored as a model photocatalytic reaction. The proposed structure of LEDs with TiO2 /SiO2 nanodisk/pedestal array exhibited a photocatalytic activity that was three times higher than the activity of LEDs with a TiO2 planar layer. The integration of photocatalytic materials with near-UV LEDs in a single system is promising for various purification applications, such as sterilization and disinfection.